(untitled) (ART AND CULTURE BULLETIN, 2026)
In this scientific article, the professional role, functional duties, and creative responsibility of the sound engineer in the process of effective organization of cultural events are analyzed from a scientific-theoretical and practical point of view. The role of the sound director in influencing the technical knowledge, managing the acoustic environment, balancing the voices of the participants in stage processes, and influencing the psychology of the audience is highlighted based on specific facts. The article reveals the organizational, technological, and creative activities of the sound engineer through examples of various cultural events (concerts, theatrical performances, public holidays, conferences). Also, the development of modern sound technologies and their impact on the quality of cultural events are analyzed on a scientific basis.